Allegro Barbaro : Béla Bartók und die bildende Kunst. - Wilhelm-Lehmbruck-Museum, Duisburg; Kunstmuseum Hannover; Sammlung Sprengel, Hannover (Duisburg : Wilhelm-Lehmbruck-Museum, 1981)
Balla, Margit ; Csohány, Kálmán ; Czinke, Ferenc ; Engelsz, József ; Feledy, Gyula ; Gyarmathy, Tihamér ; Hajdu, Etiénne ; Hencze, Tamas ; Hetey, Katalin ; etc.
Allegro Barbaro : Béla Bartók und die bildende Kunst, Wilhelm-Lehmbruck-Museum, Duisburg, 8.Februar - 15. März 1981 / Kunstmuseum Hannover mit Sammlung Sprengel, Hannover, 25. März - 14. Mai 1981
boek